CDC20B is required for deuterosome-mediated centriole production in multiciliated cells. Issue 1 (December 2018) - Revinski, Diego; Zaragosi, Laure-Emmanuelle; Boutin, Camille; Ruiz-Garcia, Sandra; Deprez, Marie; Thomé, Virginie; Rosnet, Olivier; Gay, Anne-Sophie; Mercey, Olivier; Paquet, Agnès; Pons, Nicolas; Ponzio, Gilles; et al.
Abstract Multiciliated cells (MCCs) harbor dozens to hundreds of motile cilia, which generate hydrodynamic forces important in animal physiology. In vertebrates, MCC differentiation involves massive centriole production by poorly characterized structures called deuterosomes. Here, single-cell RNA sequencing reveals that human deuterosome stage MCCs are characterized by the expression of many cell cycle-related genes. We further investigated the uncharacterized vertebrate-specificcell division cycle 20B (CDC20B ) gene, which hosts microRNA-449abc. We show that CDC20B protein associates to deuterosomes and is required for centriole release and subsequent cilia production in mouse andXenopus MCCs. CDC20B interacts with PLK1, a kinase known to coordinate centriole disengagement with the protease Separase in mitotic cells. Strikingly, over-expression of Separase rescues centriole disengagement and cilia production in CDC20B-deficient MCCs. This work reveals the shaping of deuterosome-mediated centriole production in vertebrate MCCs, by adaptation of canonical and recently evolved cell cycle-related molecules. In vertebrate multiciliated cells, most centrioles are synthesized and released by poorly characterized structures called deuterosomes. Here, the authors report that the previously-uncharacterized Cdc20b in mouse andXenopus associates with deuterosomes and contributes to centriole release.